Role of Social Media in Banking - Kazi, Zaid (2010)
Social Media management has become a crucial part of the strategy for most businesses today. Executives, marketers and consultants, are all constantly making efforts to find ways of having a presence in the social media that could help in business relationship management and thus profitability. Further, with changing consumer behaviour and ever increasing popularity of the medium, it can no longer be ignored by organisations. Although, banks are aware that they need to have a good presence on social media and make the best use of mediums such as LinkedIn, Facebook, YouTube, blogs and discussion forums; very few know how exactly to deal with it. There also seems to be confusion amongst most on what exactly Social Media is. At the same time a few banks have capitalised on the opportunities presented and established a strong presence on the Social Media domain. This study aims at uncovering the mystery of social media and understanding its role in banking. The study also reviews the social media campaigns of the global banks. Finally Standard Chartered Bank’s presence on social media is reviewed and recommendations are made.